2017
DOI: 10.1016/j.ijscr.2017.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach in thymectomy: Our experience and review of the literature

Abstract: AimThymectomy is the main treatment for thymoma and patients with myasthenia gravis (MG). The traditional approach is through a median sternotomy, but, recently, thymectomy through minimally invasive approaches is increasingly performed. Our purpose is an analysis and discussion of the clinical presentation, the diagnostic procedures and the surgical technique. We also consider post-operative complications and results, over a period of 5 years (May 2011–June 2016), in thymic masses admitted in our Thoracic Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
22
1
Order By: Relevance
“…The current results of our study found that there is no difference between BTT and TS concerning complete stable remission, while the results of two other studies [ 7 , 16 ] indicated that VATS has more complete stable remission compared to TS. Our results also reported no statistical difference between the two groups regarding pharmacological remission, which disagrees with Bachmann et al [ 1 ], who mentioned that VATS has less pharmacological remission than TS.…”
Section: Discussioncontrasting
confidence: 69%
“…The current results of our study found that there is no difference between BTT and TS concerning complete stable remission, while the results of two other studies [ 7 , 16 ] indicated that VATS has more complete stable remission compared to TS. Our results also reported no statistical difference between the two groups regarding pharmacological remission, which disagrees with Bachmann et al [ 1 ], who mentioned that VATS has less pharmacological remission than TS.…”
Section: Discussioncontrasting
confidence: 69%
“…After complete resection, patients with thymoma have a very low rate of recurrence. [ 28 29 30 ] Unlike other malignant tumors, such as lung cancer, most recurrences or metastases of thymoma happened in pleural cavity. There were also occasional recurrences or metastases to lung or liver.…”
Section: Discussionmentioning
confidence: 99%
“…All soft tissue should be removed in the anterior mediastinum between the phrenic nerves, which is key to control patients who present with myasthenia gravis and positively impact in mortality. [17,18]. Thoracoscopy was the most utilized approach in our patients (66.6%), as it is minimally invasive and signi cantly reduces complication rate.…”
Section: Discussionmentioning
confidence: 94%